How Do Uterine Natural Killer and Innate Lymphoid Cells Contribute to Successful Pregnancy? - Huhn, Oisín; Zhao, Xiaohui; Esposito, Laura; Moffett, Ashley; Colucci, Francesco; Sharkey, Andrew M. (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILCs) are the most abundant immune cells in the uterine mucosa both before and during pregnancy. Circumstantial evidence suggests they play important roles in regulating placental development but exactly how they contribute to the successful outcome of pregnancy is still unclear. Uterine ILC (uILCs) include subsets of tissue-resident natural killer (NK) cells and ILCs, and until recently the phenotype and functions of uILCs were poorly defined. Determining the specific roles of each subset is intrinsically challenging because of the changing nature of the tissue both during the menstrual cycle and pregnancy. Single-cell RNA sequencing (scRNAseq) and high dimensional flow and mass cytometry approaches have recently been used to analyse uILC populations in the uterus in both humans and mice. This detailed characterisation has significantly changed our understanding of the heterogeneity within the uILC compartment. It will also enable key clinical questions to be addressed including whether specific uILC subsets are altered in infertility, miscarriage and pregnancy disorders such as fetal growth restriction and pre-eclampsia. This review focuses on recent advances in our understanding of the phenotypic and functional diversity of uILCs in non-pregnant endometrium and first trimester decidua and on how these cells may contribute to a successful pregnancy.